Heart Disease Detection Using Data Miningtechniques - Anikumar, Akhila; Shajan, Shajan PX (International Journal of Computer Sciences and Engineering, 2025)
Data mining is process to analyses number of data sets and then extracts the meaning of data. It helps to predict the patterns and future trends, allowing business in decision making. Data mining provides methods and techniques for transformation of the data into useful information for decision making. These techniques can make process fast and take less time to predict the heart disease with more accuracy. In this paper we survey different papers in which one or more algorithms of data mining used for the prediction of heart disease. By Applying data mining techniques to heart disease data which requires to be processed, we can get effective results and achieve reliable performance which will help in decision making in healthcare industry. It will help the cardiologist to diagnose the disease in less time and predict probable complications well in advance